Juridical Analysis of Dispute Resolution Between Patients and Doctors Based on Indonesian Positive Law - Daniel Thomas Suryadisastra; Nanda Dwi Rizkia; Hardi Fardiansyah (PT FORMOSA CENDEKIA GLOBAL, 2023)
Health law is a relatively new legal specialty in Indonesia. Humanely speaking, doctors as human beings certainly cannot be separated from carelessness and fatigue. It is hoped that the Law “No. 29 of 2004” concerning Medical Practice can provide legal protection and certainty as stipulated in “Article 50 (a) which reads: “Doctors or dentists who practice medicine have the right to receive legal protection while carrying out their duties. task.